Efektivitas Terapi Latihan terhadap Peningkatan Kemampuan Fungsional Lutut pada Kasus Dislokasi Patella Dextra di RS Efarina Pematangsiantar - Fujastawan, I Ngurah Gede Verar; Herawati, Noni; Hasibuanlumbantoruan, Jesicca (Jurnal Riset Hesti Medan, 2025)
Patellar dislocation is a category of joint instability with a combined movement pattern of slight rotation accompanied by the impact on the valgus side. Various problems that arise include pain and spasm, knee instability, decreased ROM, and functional limitations. Exercise therapy in the form of active static stretching exercise, core exercise, and CKCE is estimated to improve functional ability by reducing pain and spasm, increasing knee stability, and increasing ROM. This study aimed to determine the effectiveness of exercise therapy on improving the functional ability of the knee. Methods: A single case study implementing a physiotherapy intervention on a 20-year-old woman with a right patellar dislocation. Static stretching exercises and CKCE were given twice per week, while core exercise was given three times a week. Each intervention was evaluated four times using various parameters. Pain intensity using VAS, ROM using Goniometer, and assessment of functional ability using Kujala and NPI scores. Results: There is a decrease in pain and an increase in ROM and functional ability using the Kujala and NPI Score. Conclusion: This study shows that stretching exercise, core exercise, and CKCE can improve the functional ability of the knee in the case of right patellar dislocation as measured using functional parameters Keywords: Patellar dislocation, static stretching exercise, core exercise, CKCE